Bivalve abundances in shallow coastal bays in Northern Bohuslän - Bergström, Per (University of Gothenburg, 2025)
Abundance of bivalves in shallow soft-bottom in the area around Tjärnö, Rossö and Öddö in the Northern part of Bohuslän (Data_bivalves). Data from 25 sites that have been sampled by 5 replicate each. Data for individual replicates are given in number of individuals per square meter. Coordinates of sites and date of sampling in separate file (Data_sites). Sampling by pushing a plastic core (31cm diameter) 20 cm into the sediment and all material dug out and sieved through a 4mm mesh. Species names updated to current valid names on March 25th, 2025 . Data collected as part of degree project. Dataset publication was supported by Mistra Co Creating Better Blue (C2B2).

Abundans av diverse olika musselarter i grunda mjukbottnar i området kring Tjärnö, Rossö och Ödde i Norra Bohulsän (Data_bivalver). Data från 25 lokaler vilka provtagits med 5 replikat vardera. Data för enskilda replikat anges i antal individer per kvadratmeter. Lokalers koordinater och datum för provtagning finns i separat fil (Data_sites). Provtagning har utförts genom att ett plaströr med diametern 31 cm har tryckts ner 20cm i sedimentet och allt material inom röret har grävts ur och sållats genom ett såll med 4mm maskstorlek. Arternas namn har uppdaterats till nuvarande gällande namn den 25 mars 2025. Data insamlat som del av examensarbete. Publiceringen av datasetet stöddes av Mistra Co Creating Better Blue (C2B2).
Abundans av musslor på grunda mjukbottnar i norra Bohuslän
Keywords: Species distribution; Arters utbredning; bivalvia; musslor; Mytilus edulis; blåmussla; Scrobicularia plana; plan pepparmussla; Polititapes aureus; gyllene venusmussla; Macomangulus tenuis; färgvariabel skivmussla; Timoclea ovata; radiärstrimmig venusmussla; Cerastoderma glaucum; skev hjärtmussla; Petricolaria pholadiformis; Cerastoderma edule; ätlig hjärtmussla; Venerupis corrugata; silkesslät venusmussla; varicorbula gibba (olivi, 1792); shallow soft-bottom; Grunda mjukbottnar; Macoma balthica; Ensis sp.; Ecology; Ekologi; Biota; Biologi och ekologi